STUDIES ON PHYTOCHEMICAL SCREENING, TANNINS CONTENT AND ANTIBACTERIAL ACTIVITY FROM LEAF AND CALLUS EXTRACTS OF MEMECYLON UMBELLATUM. - ANBUKKARASI M; R, Dhamotharan; JANARTHANAM B (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aims to determine the phytochemical screening, tannins content, and antibacterial activity from leaf and callus extracts of Memecylon umbellatum. Methods: Preliminary screening involved the qualitative methods to detect the presence of terpenoids, flavonoids, phenols, tannins, steroids, quinones, saponins, cardiac glycosides, and alkaloids. Total tannins contents were quantitatively estimated with tannic acid as standard. Different concentrations of ethanolic leaf and callus extracts were tested using the agar disc diffusion technique for the antibacterial activity against Bacillus subtilis, Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. Results: The phytochemical analysis of leaf and callus extract of M. umbellatum revealed the presence of significant secondary metabolites such as tannins, saponins, quinones, cardiac glycosides, phenols, flavonoids, terpenoids, steroids, and alkaloids. The total tannins content in callus and leaf extract were found to be 11.37 mg tannic acid equivalents (TAE)/g and 7.1 mg TAE/g, respectively. The antibacterial activity of ethanolic leaf and callus extracts of M. umbellatum shown more active against B. subtilis. Both the callus and leaf extract of M. umbellatum was found to be inactive against E. coli. Conclusion: It was concluded that the powerful antibacterial effect is attributed to the greater amount of tannin compounds in the ethanolic callus extracts of M. umbellatum. Â 